Incorporating silica-coated graphene in bioceramic nanocomposites to simultaneously enhance mechanical and biological performance - Li, Zhong (2022)
The applications of a variety of bioactive ceramics such as hydroxyapatite (HA) in orthopedics are limited by their insufficient mechanical properties, especially poor fracture toughness. Thus, further extending the clinical applications of these materials warrants the enhancement of their mechanical properties. Although the reinforcement of ceramics by 2D nanomaterials has been well recognized, integrated structural, mechanical, and functional considerations have been neglected in the design and synthesis of such composite materials. Herein, we report the first use of silica-coated reduced graphene oxide (S-rGO) hybrid nanosheets to create bioceramic-based composites with simultaneously enhanced mechanical and biological properties. In the representative HA-based bioceramic systems prepared by spark plasma sintering, S-rGO incorporation was found to be more effective for increasing the Young's modulus, hardness, and fracture toughness than the incorporation of uncoated reduced GO (rGO). Furthermore, when assessed with osteoblast-like MG-63 cells, such novel materials led to faster cell proliferation and higher cell viability and alkaline phosphatase activity than are generally observed with pure HA; additionally, cells demonstrate stronger affinity to S-rGO/HA than to rGO/HA composites. The S-rGO/bioceramic composites are therefore promising for applications in orthopedic tissue engineering, and this research provides valuable insights into the fabrication of silica-coated hybrid nanosheet-reinforced ceramics.